Roaming beyond the fence - Tunku Zain Al-'Abidin ibni Tuanku Muhriz (Singapore : Editions Didier Millet Pte Ltd., 2013)
'This is a collection of Tunku'Abidin's columns published in The Star newspaper, with additional articles and speeches. His writing addresses many key concerns of Malaysians : from English in education, corruption and freedom of the press to public transport, Ramadhan buffets and potholes'
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid
Keywords: Malaysia -- Politics and government; Malaysia -- Social conditions; Malaysia -- Miscellanea; Malaysia -- Kings and rulers